Phytochemical constituents and toxicity analysis of ethanolic ketapang (Terminalia catappa L.) leaf extract - Kierrthanah Madhavan; Yaya Rukayadi; Noor Azira Abd Mutalib (Penerbit Universiti Kebangsaan Malaysia, 2023)
Terminalia catappa L., which is also known as Indian almond, tropical almond, and ketapang, belongs to the family of Combretaceae and it forms layers of canopy, which provides shade to locals. The parts of the plant such as bark, fruit, leaf, rhizomes, and roots have been traditionally used in folk medicines for several treatment purposes, demonstrating its numerous biological activities. The current study evaluated phytochemical constituents in its leaf responsible for its biology activities and toxicity analysis by brine shrimp lethality test for ethanolic leaf extract of T. catappa L. (EKLE) to set a safe limit for future applications in studies. Phytochemical compounds such as squalene, phytol, DL-α-tocopherol, β-sitosterol, stigmasterol, α-amyrin, and β-amyrin were identified in EKLE through GC-MS analysis, which is believed to contribute to its biology activities such as antibacterial. This is the first time to report β-sitosterol in the leaf of T. catappa L., though previous studies have reported in the bark of the tree and other parts of its genus. This is the first time to identify β-amyrin in this tree. The LC50 value in the brine shrimp assay was above 100 µg/mL, suggesting the extract is biologically safe and non-toxic for humans. However, the application of the extract shall not be more than 11.61 mg/mL.